Breast cancer and public healthcare: survey and proposals from Brazilian Society of Mastology (SBM) - Hassan, Augusto Tufi; Bessa, Jordana de Faria; Novita, Guilherme Garcia; Gioia, Sandra; Mattar, André; Cavalcante, Francisco Pimentel; Freitas-Junior, Ruffo; Ruiz, Carlos Alberto (Mastology, 2024)
Introduction: High rates of breast cancer mortality have been reported for patients from public healthcare, in Brazil. This study aimed to obtain a panorama of breast cancer in public healthcare, based on a questionnaire sent to breast specialists. Methods: Active members of the Brazilian Society of Mastology (SBM) were invited to participate anonymously, from Aug-Oct 2023. Possible answers ranged from “This is not a problem” to “This is a very serious, very common problem”. The primary endpoint of the study was the relative frequency of the answers. Results: Overall, 767 (44% of all SBM affiliated members) completed the questionnaire. Access to modern drugs was considered the most concerning problem, with 81.36% of respondents classifying this as “serious, frequently” or “very serious, very frequently”, followed by access to diagnostic methods (64.53%), access to breast reconstruction (60.24%), delay in starting treatment (60.11%) and access to screening (51.76%). Conclusions: This is the first study to evaluate the perceptions of breast specialists on breast cancer care within SUS. The SBM has issued considerations and proposals aimed at reestablishing a minimally adequate standard of breast cancer diagnosis and treatment in public healthcare in Brazil.